A Case of Primary Cardiac B-cell Lymphoma Diagnosed with Cardiac MRI - Kevin Lee; Iva Minga; Eryn Cameron; Juan Pablo Salazar Adum; Amit Pursnani (US Cardiology Review)
Primary cardiac tumors account for only 0.3% of all cardiac tumors; of these, lymphomas account for only 2% of all primary cardiac tumors. Cardiac lymphomas have a grim prognosis, often less than 1 year due to delays in diagnosis and treatment. Cardiac MRI is the gold standard for the imaging of cardiac tumors. We describe the case of a 76-year-old man with no significant past medical history who presented to the emergency department with a large pericardial effusion that was found to be consistent with cardiac lymphoma on cardiac MRI prior to tissue diagnosis of a primary cardiac diffuse large B-cell lymphoma. The clinical and radiological features of cardiac lymphoma are reviewed, and the therapeutic management and side-effects that the patient experienced are discussed.